2016
DOI: 10.7150/ijbs.16430
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-secretase Inhibitor Prevents Proliferation and Migration of Ductus Arteriosus Smooth Muscle Cells through the Notch3-HES1/2/5 Pathway

Abstract: Patent ductus arteriosus (PDA) can cause morbidity and mortality in neonates. Vascular remodeling, characterized by proliferation and migration of smooth muscle cells (SMCs), is an essential process for postnatal DA closure. Notch signaling is an important mediator of vascular remodelling but its role in DA is unkonwn. We investigated the effects and underlying mechanisms of γ-secretase inhibitor DAPT, a Notch signaling inhibitor on angiotensin II (Ang II)-induced proliferation and migration of DASMCs. Prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Many studies suggest that Notch is necessary for maintaining VSMCs in a contractile/quiescent phenotype. In rat VSMCs, the IL-1β-induced secretory/migrating phenotype is blunted by Notch-3 overexpression and enhanced by treatment with DAPT, a γ-secretase inhibitor [259] but, contrary to this finding, DAPT also seems to prevent SMC migration and proliferation induced by AngII [260].…”
Section: Notch In Vascular Smooth Muscle Cellsmentioning
confidence: 69%
“…Many studies suggest that Notch is necessary for maintaining VSMCs in a contractile/quiescent phenotype. In rat VSMCs, the IL-1β-induced secretory/migrating phenotype is blunted by Notch-3 overexpression and enhanced by treatment with DAPT, a γ-secretase inhibitor [259] but, contrary to this finding, DAPT also seems to prevent SMC migration and proliferation induced by AngII [260].…”
Section: Notch In Vascular Smooth Muscle Cellsmentioning
confidence: 69%
“…ERK1/2 has been shown to be an endogenous negative regulator of the γ-secretase activity by phosphorylating nicastrin, an essential component of γ-secretase; while presenilin, another key component of γ-secretase activity has been shown to be able to activate PI3K and ERK1/2 [48,49]. Using ductus ateriosus smooth muscle cells, Wu and colleagues demonstrated that DAPT inhibits cell proliferation by not only inhibiting ERK1/2 and Akt phosphorylation but also by promoting cell cycle arrest in the G0/G1-phase [50]. Collectively, these effects of single stimulation of mCRP, FGF-2 and their combination mCRP with FGF-2 on EC proliferation confirm the theory that growth factors display additive and even synergistic characteristics during early stages of angiogenesis, with the combination of at least two growth factors displaying the highest proliferation rate [51].…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of IL-15 in the ductus is mediated through the prostaglandin pathway. IL-15 upregulates the expression of EP 4 mRNA, as well as stimulating angiogenesis through binding to endothelial cells ( 91 ). In late gestation, several factors try to promote the structural closure of the ductus in preparation for the postnatal life and IL-15 may balance this tendency by a counteractive mechanism ( 92 ).…”
Section: Anatomic Closure and Remodelingmentioning
confidence: 99%
“…A decrease in the number of Notch receptors in SMCs is associated with downregulation of gene expressions related to contractile elements ( 84 ). Notch signaling is required for contractile SMC differentiation in mice ( 91 ).…”
Section: Anatomic Closure and Remodelingmentioning
confidence: 99%
See 1 more Smart Citation